Metabolic Control of Redox and Redox Control of Metabolism in Plants - Geigenberger, Peter (Mary Ann Liebert, Inc., 2014)
Significance: Reduction-oxidation (Redox) status operates as a major integrator of subcellular and extracellular metabolism and is simultaneously itself regulated by metabolic processes. Redox status not only dominates cellular metabolism due to the prominence of NAD(H) and NADP(H) couples in myriad metabolic reactions but also acts as an effective signal that informs the cell of the prevailing environmental conditions. After relay of this information, the cell is able to appropriately respond via a range of mechanisms, including directly affecting cellular functioning and reprogramming nuclear gene expression. Recent Advances: The facile accession of Arabidopsis knockout mutants alongside the adoption of broad-scale post-genomic approaches, which are able to provide transcriptomic-, proteomic-, and metabolomic-level information alongside traditional biochemical and emerging cell biological techniques, has dramatically advanced our understanding of redox status control. This review summarizes redox status control of metabolism and the metabolic control of redox status at both cellular and subcellular levels. Critical Issues: It is becoming apparent that plastid, mitochondria, and peroxisome functions influence a wide range of processes outside of the organelles themselves. While knowledge of the network of metabolic pathways and their intraorganellar redox status regulation has increased in the last years, little is known about the interorganellar redox signals coordinating these networks. A current challenge is, therefore, synthesizing our knowledge and planning experiments that tackle redox status regulation at both inter- and intracellular levels. Future Directions: Emerging tools are enabling ever-increasing spatiotemporal resolution of metabolism and imaging of redox status components. Broader application of these tools will likely greatly enhance our understanding of the interplay of redox status and metabolism as well as elucidating and characterizing signaling features thereof. We propose that such information will enable us to dissect the regulatory hierarchies that mediate the strict coupling of metabolism and redox status which, ultimately, determine plant growth and development. Antioxid. Redox Signal. 21, 1389–1421.